(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
Academic decision making is often based on research results in order to optimize the effectiveness of the choices made. Such decisions could possibly include but are not limited to the modules taught, assessment procedures, teaching methods, and admission procedures. All academic institutions aspire to create perfect instruments for a fair, equal, and criteria-based admission. The admission test for the Department of English language and literature was first used in the academic year 2019. However, there is always a desire to improve the procedures and evaluate what is currently at use. This research investigated two questions: What are the possible adjustments that could be made for the admission exam? and to what extent is the current entry exam effective? The researcher used statistics collected from the statistics and exams departments in the Faculty of Arts and Humanities in Damascus University and trend analysis to answer the research questions. The statistics showed that the currently used admission test did help in decreasing the number of learners accepted in the Faculty but it did not affect the percentage of those who fail the first year. After analyzing the on-going trends in some Faculties and Institutions in Damascus University, several models that could improve the admission process have been suggested such as: a preparatory year, the HIBA model, a multi-staged admission test, and an eclectic model. Finally, future research recommendations were made in order to highlight other aspects that need to be investigated.